Penerapan E-Procurement Dalam Proses Pengadaan Barang/Jasa Di Kabupaten Malang (Studi Pada Bidang Asset Dinas Pendapatan, Pengelolaan Keuangan dan Asset Kabupaten Malang) - Amelia Iftitah Damayanti (Jurnal Administrasi Publik, 2013)
Abstract: The Application Of E-Procurement In The Process For Procurement Of Goods /Services In Malang. The main problem being the subject of this thesis is the procurement of goods/services through electronic systems, namely e-Procurement in Malang Counties.The background was made in this study is to see how e-Procurement undertaken by Malang in particular areas of the Revenue Agency Asset Management of financial and Asset. This research uses qualitative research with type a descriptive approach.Data sources used are primary data and secondary data.This research resulted in a conclusion that e-Procurement undertaken by DPPKA in particular The Asset has not reached the maximum, it is based on research results in the field.The authors provide solutions related to the implementation of e-Procurement in the process of procurement of goods/services in Malang consists of:Dissemination of goods/services procurement process electronically (e-procurement),the need for increased cooperation from all parties for the mechanism and process of supervision, monitoring and evaluation, the provision of facilities and infrastructure adequate technology particularly as supporting system of e-Procurement. Keywords: e-Procurement, the procurement of goods/services, asset Â  Abstrak: Penerapan E-Procurement Dalam Proses Pengadaan Barang/Jasa Di Kabupaten Malang. Masalah utama yang menjadi bahasan dari skripsi ini adalah pengadaan barang/jasa melalui Sistem Elektronik yaitu e-Procurement di Kabupaten Malang. Latar belakang yang diangkat dalam penelitian ini yaitu untuk melihat bagaimana e-Procurement yang dilakukan oleh Kabupaten Malang khususnya Bidang Asset Dinas Pendapatan Pengelolaan Keuangan Dan Asset.Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan deskriptif. Sumber data yang digunakan adalah data primer dan data sekunder. Penelitian ini menghasilkan suatu kesimpulan bahwa e-Procurement yang dilakukan oleh DPPKA khususnya Bidang Asset belum mencapai maksimal, hal ini didasarkan hasil penelitian di lapangan. Penulis memberikan solusi terkait penerapan e-Procurement dalam proses pengadaan barang/jasa di Kabupaten Malang terdiri dari: Sosialisasi mengenai proses pengadaan barang/jasa secara elektronik (e-procurement),Perlu adanya peningkatan kerjasama untuk dari semua pihak dalam mekanisme dan proses pengawasan, monitoring serta evaluasi,penyediaan sarana dan prasarana teknologi yang lebih memadai khususnyasebagai penunjang sistem eâ€“Procurement. Kata kunci: e-Procurement, pengadaan barang/jasa, asset